Dataset associated with "Seasonality and source apportionment of non-methane volatile organic compounds at Boulder Reservoir between 2017 and 2019" - Pollack, Ilana B.; Helmig, Detlev; O'Dell, Katelyn; Fischer, Emily V. (Colorado State University. Libraries, 2020)
Multiyear observations of 13 non-methane volatile organic compounds (NMVOCs) were collected at Boulder Reservoir in the Colorado Northern Front Range Metropolitan Area (NFRMA). We separate abundances of NMVOCs into source contributions using two approaches that have been applied to prior NFRMA datasets. Positive matrix factorization (PMF) analysis identifies five NMVOC factors in winter, spring, and fall that correspond to long-lived and short-lived NMVOCs from regional oil and gas production, traffic, local shorter-lived alkenes, and regional anthropogenic background. In summer, there is an additional biogenic NMVOC factor dominated by isoprene. Over all seasons, the PMF model indicates that 57-84% (range includes uncertainties) of C2-C5 alkanes are attributed to oil and natural gas activities. Ethyne is largely from traffic with contributions ranging from 45±6% in winter to 75±21% in summer. Ethene and propene are associated with a potentially separate source of shorter-lived alkenes that we cannot identify. The largest contributing sectors to the observed hazardous air pollutants (HAPs) differ substantially by species and season. Benzene is attributed to oil and natural gas production, traffic and other industrial activities. Toluene is predominantly attributed to regional anthropogenic activities in all seasons. Of the HAPs quantified in this dataset, hexane stands out as largely attributed to oil and natural gas production. The largest differences in the attribution of sources using the two different approaches are for benzene and toluene. Consistent with prior analyses, this work shows that the NFRMA is more strongly influenced by oil and natural gas sources than many other U.S. urban regions.
Dataset containing 13 non-methane volatile organic compounds (NMVOCs) and meteorological parameters collected at Boulder Reservoir (40.0704 N, 105.2198 W, 1604 m asl), located in Boulder, Colorado between 4 April 2017 and 31 December 2019. Data are reported at the local mid time that the NMVOC sample was collected which is reported on Mountain Standard Time (MST). A flag for smoke impacted samples is also included.
Department of Atmospheric Science
Keywords: speciated volatile organic compounds; source apportionment; multivariate regression; positive matrix factorization; oil and natural gas production; Colorado northern Front Range metropolitan area